Confidentiality, anonimity?: the other promises of research - Anguita M., Verónica; Sotomayor, M. Angélica (Acta Bioethica, 2011)
It is frequent that in social or biomedical research certain expressions are used as synonymous, even having different meanings. This is the case of “anonymous” and “confidential”. Being diverse concepts, they have in common to refer to an information considered to be susceptible of protection, since knowledge by third parties may damage the owner of the information. In many cases, the equivalent use of the words “anonymous”, “confidential” or “reserved” plays against the adequate design and study outcomes, since anonymity is promised to research subjects, when it is impossible to comply.